Irish political prisoners, 1848-1922 : theatres of war - McConville, Seán (Routledge, 2003)
This is the most wide-ranging study ever published of political violence and the punishment of Irish political offenders from 1848 to the founding of the Irish Free State in 1922. Those who chose violence to advance their Irish nationalist beliefs ranged from gentlemen revolutionaries to those who openly embraced terrorism or even full-scale guerilla war.Seán McConville provides a comprehensive survey of Irish revolutionary struggle, matching chapters on punishment of offenders with descriptions and analysis of their campaigns. Government's response to political violence was determined by.